PENGARUH PEMBERIAN INSENTIF DAN LINGKUGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT UTD CREATION PACKAGING SOLUTIONS BATAM - Elsa Martha Murni Gratchia Saragih; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the effect of incentive and work environment on the spirit of work partially and simultaneously. The research method used is descriptive quantitative analysis obtained from the results of questionnaires distributed to 84 respondents to employees of PT UTD Creation Packaging Solutions Batam. Types and data sources using primary data and secondary data, measurement collection techniques using the likert scale. From data analysis that includes validity tests, realibility tests, multiple linear regression analysis, determination analysis, and significance tests with t (partial) tests, and F (simultaneous) tests. The results of this study showed that the effect of providing incentive on employee spirit of work that is t count (4,262) > t table (1.66320), meaning that the incentive had a significant effect on employee spirit of work. Second, the effect of work environment on employee spirit of work that is t count (4,970) > t table (1.66320), meaning that work environment has significant effect on employee spirit of work. The results of the F test, effect of incentive and work environment on the spirit of work is F count (57,423) > F table (3,11), means that incentive and work environment simultaneously has significant effect on employee spirit of work. Keywords: Incentive Providing, Work Environment, Work Spirit